Developmental model of suicide trajectories. (2nd January 2018) - Séguin, Monique; Beauchamp, Guy; Robert, Marie; DiMambro, Mélanie; Turecki, Gustavo
Abstract : Background: Most developmental studies on suicide do not take into account individual variations in suicide trajectories. Aims: Using a life course approach, this study explores developmental models of suicide trajectories. Method: Two hundred and fourteen suicides were assessed with mixed methods. Statistical analysis using combined discrete-time survival (DTS) and growth mixture modelling (GMM) generated various trajectories, and path analysis (Mplus) identified exogenous and mediating variables associated with these trajectories. Results: Two groups share common risk factors, and independently of these major risk factors, they have different developmental trajectories: the first group experienced a high burden of adversity and died by suicide in their early 20s; and the second group experienced a somewhat moderate or low burden of adversity before they took their own life. Structural equation modelling identified variables specific to the early suicide trajectory: conduct and behavioural difficulties, social isolation/conflicts mediated by school-related difficulties, the end of a love relationship, and previous suicide attempts. Conclusions: Psychosocial adversity between 10 and 20 years of age may warrant key periods of intervention.